Od studija knjižničarstva do studija informacijskih znanosti i pokreta iSchools - Aparac-Jelušić, Tatjana (Monografija u povodu 20 godina rada Odjela za informacijske znanosti u Zadru, 2025)
In this paper, we intend to problematize the challenges, approaches, misconceptions and different solutions that characterized the education of librarians. The emphasis is on critical observations of those efforts that a) either pointed to the efforts to neglect of the need for academic education of librarians, and even the abolition of such educational programs; or b) found that the newly emerging disciplines of Information Science and Library and Information Science, and later the establishment of the iSchools movement, are panaceas that will optimally solve the observed problems and inconsistencies in the scientific argumentation of the cognitive institutionalization of both librarianship, documentation, archival science and related disciplines, as well as “all-unifying” Information Science. In this review, efforts were made to position Croatian experiences in the education of librarians in relation to trends in Europe and America.